PENGARUH PERUBAHAN KEBIJAKAN GIRO WAJIB MINIMUM DAN INTERNAL PERBANKAN TERHADAP TINGKAT PROFITABILITAS BANK: STUDI PADA BANK PERSERO DI INDONESIA PERIODE 2011:3 – 2014:4 - Prasetyo, Tri Utomo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study examines the effect of reserve requirements changes and bank-specific factors on the profitability of Indonesian state-owned banks. The bank profitability is measured by return on assets (ROA) and return on equity (ROE). Fixed effect model is used in order to analyze the balanced panel data. The result shows that the reserve requirements changes only affect ROE, negatively and significantly. NPL has a negative and significant effect on both ROA and ROE, while NIM has a positive and singifikan effect. Deposits has a positive and significant effect on ROE, while loans has a negative and significant effect. These results suggest that banks respond negatively to the increse in reserve requirements, even though not quite much. It is because banks can maintain their interest income. On the other side, the negative relationship between loans and profitability suggests that banks cannot manage to regain their own resources that have been lent to their customers. It indicates a poor credit quality. Keywords: reserve requirements changes, bank profitability, Indonesian state-owned banks